Vladimir Nikolaevich Vargin – the founder of agronomy science in Perm province - Korlyakov, K.N.; Zubarev, Yu. N. (Perm Federal Research Centre Journal, 2023)
The article looks into the life path and scientific heritage of Vladimir N. Vargin, the outstanding scientist in the field of agriculture and the organizer of experimental institutions in Perm province. The main achievements of all agronomic and scientific activities of Professor V.N. Vargin are the organization of state agronomic service in Perm province, development of scientific and methodological base for research, programs and methods for field experiments on the cultivation of poor soddy-podzolic soils in the Urals, creating a network of experimental agricultural institutions in Perm province, promotion and implementation of perennial grasses, rational use of fertilizers, multifield crop rotations with red clover instead of extensive three-field farming systems, as well as many years of teaching at Perm University. Vladimir Vargin is the author of the textbook «Elementary Course of General Agriculture», which for a long time was a widespread manual in agricultural schools in Russia, and four monographs. In total, he published more than 150 works on agronomy, organization and economics of agriculture.